No Casual Relationship Between T2DM and the Risk of Infectious Diseases: A Two-Sample Mendelian Randomization Study - Wang, Huachen; Guo, Zheng; Zheng, Yulu; Yu, Chunyan; Hou, Haifeng; Chen, Bing (Frontiers in Genetics, 2021)
BACKGROUND In epidemiological studies, it has been proven that the occurrence of type 2 diabetes mellitus (T2DM) is related to an increased risk of infectious diseases. However, it is still unclear whether the relationship is casual. METHODS We employed a two-sample Mendelian randomization (MR) to clarify the causal effect of T2DM on high-frequency infectious diseases: sepsis, skin and soft tissue infections (SSTI), urinary tract infections (UTI), pneumonia, and genito-urinary infection (GUI) in pregnancy. And then, we analyzed the genome-wide association studies (GWAS) meta-analysis of European-descent individuals and conducted T2DM-related single nucleotide polymorphisms (SNPs) as instrumental variables (IVs) that were associated with genome-wide significance (P < 5×10−8). MR estimates were obtained using the inverse variance weighted (IVW), the Mendelian randomization-Egger (MR-Egger) regression，the simple mode (SM)，weighted median and weighted mode. RESULTS The UK Biobank (UKB) cohort (n>500 000) provided data for GWASs on infectious diseases. MR analysis showed little evidence of a causal relationship of T2DM with five mentioned infections (sepsis, SSTI, UTI, pneumonia and GUI in pregnancy) susceptibility (odds ratio [OR]= 0.99999, P=0.916 ; OR, 0.99986; P=0.233; OR, 0.99973; P=0.224; OR, 0.99997; P=0.686; OR, 1.00002; P=0.766). Sensitivity analysis showed similar results, indicating the robustness of causality. There was no heterogeneity and pleiotropic bias. CONCLUSION T2DM would not be causally associated with high-frequency infectious diseases (including sepsis, SSTI, UTI, pneumonia, GUI in pregnancy).